Experimental Evaluation on Physical and Mechanical Properties of Concrete Containing Green Mussel Shell (Perna viridis) Powder as an Admixture - Sainudin, Muhammad Shabery; Othman, Nor Hazurina; Nickholas Anting Anak Guntor, Nickholas Anting Anak Guntor; A. Khalid, Nur Hafizah; Mohd-Salleh, Siti Nor Aishah (uthm, 2023)
Mussel shell is a type of waste that is generated abundantly. However, the presence of chemical components such as calcium (CaCO3) in mussel shells has shown its potential as filler materials in concrete designing. Therefore, this paper presents the experimental result for the physical and mechanical properties of concrete containing 1%, 2%, 3% and 4% Mussel Shell Powder (MSP) as additional material under 2.73% sodium chloride solution. The MSP has been cleaned, grinded and sieved 75μm sizes in order to obtain its final product. Compressive strength, split tensile, and capillary water absorption were determined. Statistical analysis was performed to investigate the correlation and level of significance using IBM SPSS in determining the optimal mix design for modified concrete. The performance of MSP concrete and control specimens are the main factor that been observed in this study. The increment percentages of MSP in concrete had led to reduce on its mechanical strength, however improved in its absorption rates. According to statistical analysis, it shows that low MSP percentages giving a significant value for compressive strength and very strong correlation coefficient compared to control specimens, thus it indicated minimum MSP percentages are more potential in improving concrete physical and mechanical performance.